Development of Antibiotic Resistance, Suggestion For The Safety of Our Future Generation (KYAMC Journal, 2021)
Background: Rising of multidrug resistance among uropathogenic bacteria is leading our future generation to a crisis. Nevertheless, the era of antibiotic failure due to bacterial resistance has brought interest to other medical science like Traditional Medicine, alternative medicine.Objectives: This study was undertaken to determine the current antibiotic resistance situation among common bacterial uropathogens and suggesting prevention measure.Materials and Methods: A total of 212 patients male 132,female 80 selected. Mid-urine samples were collected. Isolated organisms were identified by conventional methods. Then different antibiotics representing different families of antibiotics were tested on isolated organisms.Results: The most frequently isolated gram negative bacteria was E.Coli (92%) followed by Staphylococcus(7.07%),Klebsiella(7%), Pseudomonas(4.25%). Resistance to Amoxicilline, Ciprofloxacin, Cefixim, Ceftriaxone, Cefuroxim, Cefradin, Cefotaxim was more than 70% of all isolates of E.Coli stains. There was relatively low resistance rate to Nitrofurantoin, Gentamycin,Imipenem, Meropenem, Amikacin, Ceftazidim . However, there was emerging resistance to Ciprofloxacin, specially for common bacteria.Conclusion: It is urgent need to make a policy for antibiotics use . We suggest all health care professional of traditional medicine and modern medicine to combat against antibiotics resistance.KYAMC Journal.2021;12(1): 32-35